2017
DOI: 10.1093/europace/eux073
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malignant arrhythmia and sudden cardiac death in takotsubo syndrome and its management

Abstract: The short- as well as the long-term prevalence and recurrence of LTAs in TTS patients is high. The long-term mortality rates were similar to the TTS patients presenting without any LTAs. LTAs in TTS could be triggered by a concomitant atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 22 publications
5
51
0
1
Order By: Relevance
“…28 Besides the negative role of inflammation in athero-thrombotic burden, systemic inflammation could also pave the way to arrhythmias as observed in the early phase, possibly causing fatal events. [29][30][31][32] Altogether, the present data identify SIRS patients as a vulnerable high-risk subgroup requiring close follow-up. Along these lines, therapies to attenuate SIRS in TTS represent an appealing subject for future research.…”
Section: Discussionsupporting
confidence: 51%
“…28 Besides the negative role of inflammation in athero-thrombotic burden, systemic inflammation could also pave the way to arrhythmias as observed in the early phase, possibly causing fatal events. [29][30][31][32] Altogether, the present data identify SIRS patients as a vulnerable high-risk subgroup requiring close follow-up. Along these lines, therapies to attenuate SIRS in TTS represent an appealing subject for future research.…”
Section: Discussionsupporting
confidence: 51%
“…Eight studies were excluded because they did not report numbers of patients with AF among the death group. One was excluded due to the same database (El‐Battrawy, Lang, Ansari, Tulumen et al ( ). Three were excluded because there was no outcome of interest.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some studies suggested a noticeable association between AF and fatal arrhythmia. El‐Battrawy, Lang, Ansari, Tulumen, et al () portrayed that there was a high likelihood of the occurrence of fatal arrhythmias in patient with AF. Dip et al noticed a higher prevalence of AF among patients with life‐threatening arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Die intraoperativen EKG-Veränderungen könnten bereits durch die frühe mikrozirkulatorische Dysfunktion und transiente koronararterielle Spasmen hervorgerufen worden sein [1]. Dass mit Verzögerung dennoch die Diagnose eines TTS gelang, war insofern bedeutsam, da bei jedem fünften Patienten in der akuten Phase mit lebensbedrohlichen Komplikationen zu rechnen ist, insbesondere mit einem kardiogenen Schock sowie malignen Herzrhythmusstörungen [2,3]; diese machen die durchgängige EKG-Überwachung in dieser Phase unabdingbar [12]. Patienten mit der apikalen Form des TTS und physischem Trigger haben dabei das höchste Risiko für Komplikationen in der Initialphase [13,14].…”
Section: Diskussionunclassified